A Derivation of the Underlying Constructs of Just-In-Time Management Systems - Davy, Jeanette A.; White, Richard E.; Merritt, Nancy J.; Gritzmacher, Karen (Academy of Management Journal, 1992)
Researchers have recommended that the theoretical constructs underlying just-in-time (JIT) management systems be identified and developed if JIT is to be fully understood and its full capabilities realized. In this study, we advanced this conceptual development through an instrument based on the relevant literature and empirically deriving three underlying constructs: (1) operating structure and control, (2) product scheduling, and (3) quality implementation. We report a content analysis of these constructs and develop propositions regarding their relationships, predecessors, and outcomes.